2015
DOI: 10.1186/s40463-015-0098-y
|View full text |Cite
|
Sign up to set email alerts
|

3-phase dual-energy CT scan as a feasible salvage imaging modality for the identification of non-localizing parathyroid adenomas: A prospective study

Abstract: ObjectivesAccurate pre-operative imaging of parathyroid adenomas (PAs) is essential for successful minimally invasive surgery; however, rates of non-localizing PAs can be as high as 18 %. Multiphasic dual-energy CT (DECT) has the potential to increase accuracy of PA detection by enabling creation of paired material maps and spectral tissue characterization. This study prospectively evaluated the utility of 3-phase DECT for PA identification in patients with failed localizatio n via standard imaging.MethodsPati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…The recurrence rate for thyroid cancer in children after thyroidectomy has varied widely in reported studies, ranging from 0 to 47%, 16 - 18 , 30 - 32 while it was 10% in this cohort. Only a few studies explored the predictors of recurrence.…”
Section: Discussionmentioning
confidence: 68%
“…The recurrence rate for thyroid cancer in children after thyroidectomy has varied widely in reported studies, ranging from 0 to 47%, 16 - 18 , 30 - 32 while it was 10% in this cohort. Only a few studies explored the predictors of recurrence.…”
Section: Discussionmentioning
confidence: 68%
“…Some previous studies reported that the virtual non-contrast (VNC) phase is not useful in DE examinations because the iodine content is subtracted from both PAs and the Thy, leaving both tissues in the same HU range [5,9,12] in contrast to real non-contrast examinations where the Thy has higher HU values due to its natural iodine content. This concurs with our own observations using VNC images (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in contrast to Forghani and Mukherji [5], we found that dual-energy data from all three phases are valuable in terms of the quantitative information they provide for the differentiation of tissues. Our arterial phase was taken after 30 seconds; previous studies have used approximately 25 seconds [5,10,12]; furthermore, our venous phase was taken after 75 seconds (compared to 45 -55 seconds in other studies). Roskies et al [12] also reported the use of an additional 85 second delay.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is partly due to the lack of randomized trials in pediatric DTC, and treatment has mainly been based on adult guidelines. However, DTC behaves differently in children in comparison to adults; the clinical presentation is more aggressive and there is a higher risk of persistent and recurrent disease after initial therapy [1, 4, 7]. Further, as the disease-specific mortality related to thyroid cancer is extremely low in children, the AJCC staging remains limited in terms of prognostic significance in this group [14].…”
Section: Introductionmentioning
confidence: 99%